2021
DOI: 10.3233/jad-210439
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low-Value Care and Its Associations with Patient-Centered Outcomes in Dementia

Abstract: Background: Low-value care (LvC) is defined as care unlikely to provide a benefit to the patient regarding the patient’s preferences, potential harms, costs, or available alternatives. Avoiding LvC and promoting recommended evidence-based treatments, referred to as high-value care (HvC), could improve patient-reported outcomes for people living with dementia (PwD). Objective: This study aims to determine the prevalence of LvC and HvC in dementia and the associations of LvC and HvC with patients’ quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Our findings emphasize that HvM is not the simple opposite of LvM. Platen et al also highlighted this issue [19], demonstrating on a data basis of patients living with dementia in Germany primary care that, in contrast to LvC, recommended HvM not guarantee a positive patient-reported outcome. Their study revealed that guideline-based prescription of memantine significantly increases the health-related quality of life.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fsupporting
confidence: 51%
See 1 more Smart Citation
“…Our findings emphasize that HvM is not the simple opposite of LvM. Platen et al also highlighted this issue [19], demonstrating on a data basis of patients living with dementia in Germany primary care that, in contrast to LvC, recommended HvM not guarantee a positive patient-reported outcome. Their study revealed that guideline-based prescription of memantine significantly increases the health-related quality of life.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fsupporting
confidence: 51%
“…A study by Platen et al demonstrates that LvM is highly present in routine care. Also, PwD receiving LvM were significantly more hospitalized and had lower quality of life [ 19 ]. However, results concerning the impact of recommended HvM remained uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a preceding study revealed that at least 31% of the PwD received low-value care, particularly Lvm associated with reduced quality of life and increased hospitalization [ 16 ]. In addition, 93% of PwD were affected by at least one drug-related problem and associated additional costs, suggesting that Lvm could also amplify adverse downstream effects for both PwD and payers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding could explain that less educated people may need more educational interventions to address specific unmet needs in their dementia care and increase adherence to the given treatment and care plan. Previous analyses [ 41 ] also revealed that PwD with polypharmacy (more than five drugs regularly taken) more likely suffer from drug-related problems and receive potentially inappropriate medication and low-value care [ 42, 43 ]. This, in turn, can result in higher hospitalization rates, lower quality of life (QoL), and thus a more increased need for interventions to address this variety of unmet needs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses [ 41 ] also revealed that PwD with polypharmacy (more than five drugs regularly taken) more likely suffer from drug-related problems and receive potentially inappropriate medication and low-value care [ 42, 43 ]. This, in turn, can result in higher hospitalization rates, lower quality of life (QoL), and thus a more increased need for interventions to address this variety of unmet needs [ 41 ]. Our analysis confirmed these findings, demonstrating that PwD with higher rates of medical drug use often requires more interventions than those with a lower number of medications.…”
Section: Discussionmentioning
confidence: 99%